Transient Elastography (FibroScan) Is Not Correlated With Liver Fibrosis but With Cholestasis in Patients With Long-Term Home Parenteral Nutrition. (August 2015) - Van Gossum, André; Pironi, Loris; Messing, Bernard; Moreno, Christophe; Colecchia, Antonio; D'Errico, Antonietta; Demetter, Pieter; De Gos, Françoise; Cazals-Halem, Dominique; Joly, Francisca
Background: Long-term home parenteral nutrition (HPN) may induce liver disorders. Transient elastography (TE) has been proposed as a noninvasive alternative to liver biopsy analysis for assessment of the progression of hepatic fibrosis to cirrhosis. The goal of this study was to compare values from TE measurements to biopsy-determined stages of histologic fibrosis in patients receiving HPN. Methods : In this multicenter prospective study, patients receiving long-term HPN (≥6 months) who required a liver biopsy for clinical reasons were included. TE (FibroScan) values for each patient were compared with the degree of hepatic fibrosis measured from biopsy specimens based on the Brunt classification. TE values were also correlated to biochemical and histologic cholestasis. Two noninvasive indices for predicting liver fibrosis (APRI and FIB-4) were also evaluated. Results : Thirty patients were included in this study (mean age, 42.1 years; 63% male). The mean duration of HPN was 100.7 months; 25 patients had a short bowel and 13 had an intestinal stoma. Biochemical cholestasis was described in 22 patients. Liver histologic features varied among these patients. There was no correlation between the values of TE and the stages of histologic fibrosis, but TE values were significantly correlated to serum bilirubin level and the severity of histologic cholestasis as well as APRI and FIB-4 scores. Conclusions : In patients with long-term HPN, TE failed to assess the degree of hepatic fibrosis. This could be due to the heterogeneity of liver histologic features observed in these patients and the presence of chronic cholestasis.